(untitled) (Revista Innova Educación, 2022)
The objective of the research was to provide a new perspective to the profile of the university evaluator, with better alternatives, purposes, and scientific-academic scope. We know that the profile of the university evaluator must meet high academic and social requirements to achieve a better educational system consistent with the social environment. However, the problem is that few evaluators are properly trained to carry out a task that involves the scientific measurement of the processes of the university community. Consequently, we propose as a thesis to redefine the work of the university evaluator with clearly marked values ​​and visions for a systematic academic advance. The research methodology has followed the analytical-reflexive qualitative approach. It is concluded that the university evaluator must be predisposed to change from methods, forms, and practices that give a better result to university education.